Relevansi Nilai Barang Terhadap Tindak Pidana Pencurian - Muhammad Djaelani Prasetya (Yuriska: Jurnal Ilmiah Hukum, 2020)
This research aims to provide prescriptions on what is the relevance of the Value of Goods toward Criminal Act of Theft and what should be done. This research is a Normative Research, with the approach was Conceptual, Statute and Case approach. Legal material itself was legislation, court rulings, legal journals, theses, and other official legal publications. The data then were analyzed qualitatively. The result of the researcher indicate that the Value of Goods as the causa prima has relevance to criminal act of theft. Misdriff or not, using regular or quick criminal procedure, both depend on the Value of Goods and the specific situation. On the other hand, the accusation of the public prosecutor has an essential role, especially in determining the loss, the specification of evidence, and the application of the Article which has implications for the consideration of judges' decisions. Finally, the high burden of cases and other problems can be prevented by strengthening the existence of misdriff through the adjustment or reconstruction of the Value of Goods until reconstruction of the Criminal Act of Theft.